2013
DOI: 10.3168/jds.2012-6435
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of inbreeding depression in Holstein cattle using whole-genome SNP markers and alternative measures of genomic inbreeding

Abstract: The effects of increased pedigree inbreeding in dairy cattle populations have been well documented and result in a negative impact on profitability. Recent advances in genotyping technology have allowed researchers to move beyond pedigree analysis and study inbreeding at a molecular level. In this study, 5,853 animals were genotyped for 54,001 single nucleotide polymorphisms (SNP); 2,913 cows had phenotypic records including a single lactation for milk yield (from either lactation 1, 2, 3, or 4), reproductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
222
3
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(265 citation statements)
references
References 29 publications
(40 reference statements)
21
222
3
11
Order By: Relevance
“…The comparison of ROH is not straightforward since different studies used different criteria in particular for the minimum length of ROH and the minimum number of SNPs involved in ROH. Furthermore, the number of SNPs, density of the SNP chip and selection criteria for SNPs used to determine the genomic inbreeding can have a huge effect on these values (Bjelland et al, 2013). Ferenčaković et al (2013a) found higher number of ROH in four analyzed cattle breeds probably because of the shorter length considered to define the ROH (>1 Mb).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The comparison of ROH is not straightforward since different studies used different criteria in particular for the minimum length of ROH and the minimum number of SNPs involved in ROH. Furthermore, the number of SNPs, density of the SNP chip and selection criteria for SNPs used to determine the genomic inbreeding can have a huge effect on these values (Bjelland et al, 2013). Ferenčaković et al (2013a) found higher number of ROH in four analyzed cattle breeds probably because of the shorter length considered to define the ROH (>1 Mb).…”
Section: Resultsmentioning
confidence: 98%
“…SNPs that did not satisfy these quality criteria were excluded. Moreover, considering that high linkage disequilibrium (LD) can lead to detection of ROH that are not Runs of homozygosity in three local cattle breeds truly IBD, LD pruning was also performed before the ROH call to increase power, as suggested by Purcell et al (2007) and applied by several authors (Howrigan et al, 2011;Bjelland et al, 2013). Therefore, unlinked SNPs were selected using -indep option of PLINK with the following parameters: 50 SNPs/window, a shift of five SNPs between windows and r 2 threshold of 0.5.…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence of mating closely related individuals, inbreeding manifests itself phenotypically as a loss in general level of performance and fitness of the progeny (Charlesworth and Willis 2009;Bjelland et al, 2013). It leads to the loss of genetic variation within population and accumulation of recessive mutations, which may be associated with several lethal effects (Bjelland et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The inbreeding coefficient is defined as the probability that a pair of alleles is identical by descent (IBD). Historically, geneticists have estimated this probability using pedigree data though genomic information should lead to a more accurate depiction (Bjelland et al, 2013). Increased levels of inbreeding would appear genomically as an increase in the frequency of homozygous alleles.…”
Section: Introductionmentioning
confidence: 99%
“…A problem with this method is that alleles that are IBD and identical by state (IBS) cannot be distinguished and are both included in this measure of inbreeding. An alternative method involving genomic runs of homozygosity (ROH) attempts to distinguish these differences and has been used in human (Kirin et al, 2010) as well as cattle genomics (Bjelland et al, 2013;Ferenčaković et al, 2013), examining population history. The ROH are consequence of inbreeding and relatively close relationships between parent pairs, especially in small endangered populations (Mészáros et al, 2015).…”
Section: Introductionmentioning
confidence: 99%